An in vitro mimic of in‐cell solvation for protein folding studies. (6th February 2020) - Davis, Caitlin M.; Deutsch, Jonathan; Gruebele, Martin
Abstract: Ficoll, an inert macromolecule, is a common in vitro crowder, but by itself it does not reproduce in‐cell stability or kinetic trends for protein folding. Lysis buffer, which contains ions, glycerol as a simple kosmotrope, and mimics small crowders with hydrophilic/hydrophobic patches, can reproduce sticking trends observed in cells but not the crowding. We previously suggested that the proper combination of Ficoll and lysis buffer could reproduce the opposite in‐cell folding stability trend of two proteins: variable major protein‐like sequence expressed (VlsE) is destabilized in eukaryotic cells and phosphoglycerate kinase (PGK) is stabilized. Here, to discover a well‐characterized solvation environment that mimics in‐cell stabilities for these two very differently behaved proteins, we conduct a two‐dimensional scan of Ficoll (0–250 mg/ml) and lysis buffer (0–75%) mixtures. Contrary to our previous expectation, we show that mixtures of Ficoll and lysis buffer have a significant nonadditive effect on the folding stability. Lysis buffer enhances the stabilizing effect of Ficoll on PGK and inhibits the stabilizing effect of Ficoll on VlsE. We demonstrate that a combination of 150 mg/ml Ficoll and 60% lysis buffer can be used as an in vitro mimic to account for both crowding and non‐steric effects on PGK and VlsE stability and folding kinetics in the cell. Our results also suggest that this mixture is close to the point where phase separation will occur. The simple mixture proposed here, based on commercially available reagents, could be a useful tool to study a variety of cytoplasmic protein interactions, such as folding, binding and assembly, and enzymatic reactions. Significance Statement: The complexity of the in‐cell environment is difficult to reproduce in the test tube. Here we validate a mimic of cellular crowding and sticking interactions in a test tube using two proteins that are differently impacted by the cell: one is stabilized and the other is destabilized. This mimic is a starting point to reproduce cellular effects on a variety of protein and biomolecular interactions, such as folding and binding.